2005
DOI: 10.3354/meps285193
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural avoidance of acidified water by juveniles of four commercial fish and prawn species with migratory life stages

Abstract: Impacts on aquatic ecosystems resulting from acute exposure to acid sulfate soil discharge are well documented. However, less is known about the long-term impacts of chronic acid sulfate discharge. Such discharge may create barriers to movement, potentially affecting migration of fish and invertebrate species, including commercial species. Avoidance of such discharges by adults may affect spawning migrations, while similar behaviour by juveniles may affect migration to nursery habitats. As a result, the capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
(20 reference statements)
2
17
0
Order By: Relevance
“…The changes in behaviour seen in the reared post-settlement fish may be a similar response due to the acidity of red soil. Behavioural avoidance of acid sulfate soils has been shown in juveniles of various fishes when pH levels were well within the range exhibited in natural systems (Kroon 2005). Red soil in Okinawa is acidic, with a pH of ~5 (Mkadam et al 2006), and analysis of the rearing conditions used here showed that the pH decreased with both increasing concentration of red soil and time.…”
Section: Discussionsupporting
confidence: 64%
“…The changes in behaviour seen in the reared post-settlement fish may be a similar response due to the acidity of red soil. Behavioural avoidance of acid sulfate soils has been shown in juveniles of various fishes when pH levels were well within the range exhibited in natural systems (Kroon 2005). Red soil in Okinawa is acidic, with a pH of ~5 (Mkadam et al 2006), and analysis of the rearing conditions used here showed that the pH decreased with both increasing concentration of red soil and time.…”
Section: Discussionsupporting
confidence: 64%
“…The relatively small impact of the tested water quality variables on immune-gene expression in adult S. glomerata was unexpected and may reflect the fact that adult oysters are intertidal euryhaline organisms that have evolved mechanisms to cope with rapid changes in their environment. The juvenile finfish Pagrus auratus, Acanthopagrus australis and Macquaria novemaculeata and the marine invertebrate prawn Metapenaeus macleayi can predict acidity and avoid low concentrations of sulfuric acid (pH 6.6 to 5.0) when given a choice (Kroon 2005). Adult S. glomerata are sessile organisms that cannot escape ASS leachate, but are likely to close their shells in an attempt to avoid the acidity and heavy metal toxicity associated with ASS leachate.…”
Section: Discussionmentioning
confidence: 99%
“…In eastern Australia, disturbance of acid sulfate soils has a well documented history of causing environmental problems including fish kills particularly in northern New South Wales Sammut et al 1996;Roach 1997;Kroon 2005;Kroon and Ansell 2006), south eastern Queensland (Preda and Cox 1998;Cook et al 2000), and at East Trinity, Cairns in north Queensland Hicks et al 1999;Cook et al 2000;Russell and Helmke 2002;Russell and McDougall 2003;Russell and Preston 2005;Russell 2006). The first records of fish kills in the vicinity of East Trinity were around 1972, not long after site reclamation works had commenced.…”
Section: Introductionmentioning
confidence: 95%